2007
DOI: 10.1038/nature05936
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a human membrane protein involved in cysteinyl leukotriene biosynthesis

Abstract: The cysteinyl leukotrienes, namely leukotriene (LT)C4 and its metabolites LTD4 and LTE4, the components of slow-reacting substance of anaphylaxis, are lipid mediators of smooth muscle constriction and inflammation, particularly implicated in bronchial asthma. LTC4 synthase (LTC4S), the pivotal enzyme for the biosynthesis of LTC4 (ref. 10), is an 18-kDa integral nuclear membrane protein that belongs to a superfamily of membrane-associated proteins in eicosanoid and glutathione metabolism that includes 5-lipoxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
158
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(169 citation statements)
references
References 30 publications
8
158
1
Order By: Relevance
“…The subunits of MPGES1 form a homotrimer ( Fig. 1) in a similar way as for the other structurally characterized MAPEG members, MGST1 (17), FLAP (18), and LTC4S (19,20) and in agreement with earlier low resolution and hydrodynamic data on MPGES1 (5). Our result thus supports the suggestion that a trimeric arrangement is common to all MAPEG proteins (21).…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…The subunits of MPGES1 form a homotrimer ( Fig. 1) in a similar way as for the other structurally characterized MAPEG members, MGST1 (17), FLAP (18), and LTC4S (19,20) and in agreement with earlier low resolution and hydrodynamic data on MPGES1 (5). Our result thus supports the suggestion that a trimeric arrangement is common to all MAPEG proteins (21).…”
Section: Resultssupporting
confidence: 75%
“…These regions were U-shaped (Fig. 3B) similar to what has been observed for GSH in LTC4S (19,20) but located deeper and at a different angle. In the vicinity of the GSH binding pocket a number of conserved residues are found that are involved in GSH binding (Fig.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…8 n-Alkyl-b-D-maltosides (C n G 2 ), which are in the focus of the present study, have been used in many cases as solubilizing agents to achieve membrane protein crystallization. Representative examples of a successful application of C 12 G 2 are photosystem I (PSI) 9 and photosystem II (PSII) [10][11][12] as well as the cytochrome (cyt) b 6 f complex 13 of oxygenic photosynthesis, a bacterial multidrug efflux transporter, 14 a cyt c quinol dehydrogenase, 15 a human leukotriene C 4 synthase, 16,17 and the rotor of V-type Na + -ATPase. 18 The homologous detergent C 11 G 2 was used in the case of the yeast cyt bc 1 complex, 19,20 C 10 G 2 for a glutamate transporter, 21 and C 8 G 2 for a chloride channel.…”
Section: Introductionmentioning
confidence: 99%